Pathway-Centric Analysis of Microbial Metabolic Potential and Expression Along Nutrient and Energy Gradients in the Western Atlantic Ocean - Cavaco, Maria A.; Bhatia, Maya P.; Hawley, Alyse K.; Torres-Beltrán, Monica; Johnson, Winifred M.; Longnecker, Krista; Konwar, Kishori; Kujawinski, Elizabeth B.; Hallam, Steven J. (Frontiers in Marine Science, 2022)
Microbial communities play integral roles in driving nutrient and energy transformations in the ocean, collectively contributing to fundamental biogeochemical cycles. Although it is well known that these communities are stratified within the water column, there remains limited knowledge of how metabolic pathways are distributed and expressed. Here, we investigate pathway distribution and expression patterns from surface (5 m) to deep dark ocean (4000 m) along a 2765 km transect in the western South Atlantic Ocean. Consistent with previous observations, we observed vertical zonation of microbial community structure largely partitioned between light and dark ocean waters. Although metabolic pathways inferred from genomic sequence information were similar across all depths, gene expression stratified with depth. For example, although photosynthetic pathways were predicted throughout the water column, gene expression increased in sunlit waters. Conversely, expression of pathways related to carbon conversion processes, particularly those involving recalcitrant and organic carbon degradation pathways (i.e., oxidation of formaldehyde) increased in dark ocean waters. We also observed correlations between indicator taxa for specific depths with the selective expression of metabolic pathways. For example, SAR202, prevalent in deep waters, was strongly correlated with expression of the methanol oxidation pathway. From a biogeographic perspective, microbial communities along the transect encoded similar metabolic potential with some latitudinal stratification in gene expression observed. For example, at a station influenced by input from the Amazon River expression of pathways related to oxidative stress was increased. Finally, when pairing distinct correlations between specific particulate metabolites (e.g., DMSP, AMP and MTA) and both the taxonomic microbial community and metatranscriptomic pathways across depth and space, we were able to observe how changes in the marine metabolite pool may be influenced by microbial function and vice versa. Taken together, these results indicate that marine microbial communities encode a core repertoire of widely distributed metabolic pathways that are differentially regulated along nutrient and energy gradients. Such pathway distribution patterns are consistent with robustness in microbial food webs and indicate a high degree of functional redundancy.